Comparison Of IPO Regimes In Korea And China (Journal of Namibian Studies : History Politics Culture, 2023)
This comparative study examines IPO systems in China and Korea, highlighting differences and commonalities within the two economies' legislative architecture, market climates, and investor safeguards. China's IPO system has moved away from a state-led process to be more market-oriented, reflecting broader market reforms. However, its regulatory emphasis stands in contrast to the largely market-oriented approach of Korea, with the latter emphasizing transparency, the rights of minority shareholders, and global access to the market. By examining premier IPOs such as Alibaba and Samsung Life Insurance, the study argues that the legal and institutional contexts in which IPOs are housed critically shape their nature, balance, and confrontations. it suggests that despite a push toward enhanced market efficiency and competitiveness, both countries continue to confront considerable challenges. The findings have implications for policy makers, investors, and companies involved in the IPO process. The study suggests a model of ongoing experimentation and a call for institutional reform that is more innovative.